Prophylactic anti-staphylococcal antibiotics for cystic fibrosis - Smyth, Alan R.; Walters, Sarah (Wiley, 2014)
Background Staphylococcus aureus causes pulmonary infection in young children with cystic fibrosis. Prophylactic antibiotics are prescribed hoping to prevent such infection and lung damage. Antibiotics have adverse effects and long-term use might lead to infection with Pseudomonas aeruginosa. Objectives To assess continuous oral antibiotic prophylaxis to prevent the acquisition of Staphylococcus aureus versus no prophylaxis in people with cystic fibrosis, we tested these hypotheses. Prophylaxis: 1. improves clinical status, lung function and survival; 2. causes adverse effects (e.g. diarrhoea, skin rash, candidiasis); 3. leads to fewer isolates of common pathogens from respiratory secretions; 4. leads to the emergence of antibiotic resistance and colonisation of the respiratory tract with Pseudomonas aeruginosa. Search methods We searched the Cochrane Cystic Fibrosis and Genetic Disorders Group Trials Register, comprising references identified from comprehensive electronic database searches, handsearches of relevant journals and abstract books of conference proceedings. Companies manufacturing anti-staphylococcal antibiotics were contacted. Most recent search of Register: 04 September 2014. Selection criteria Randomised trials of continuous oral prophylactic antibiotics (given for at least one year) compared to intermittent antibiotics given ’as required’, in people with cystic fibrosis of any disease severity. Data collection and analysis The authors assessed studies for eligibility and methodological quality and extracted data. Main results We included four studies, totaling 401 randomised participants aged zero to seven years on enrolment. The two older studies generally had a higher risk of bias across all domains, but in particular due to a lack of blinding and incomplete outcome data, than the two more recent studies. We only regarded the most recent study as being generally free of bias, although even here we were not certain of the effect of the per protocol analysis on the study results. Fewer children receiving anti-staphylococcal antibiotic prophylaxis had one or more isolates of Staphylococcus aureus. There was no significant difference between groups in infant or conventional lung function. We found no significant effect on nutrition, hospital admissions, additional courses of antibiotics or adverse effects. There was no significant difference in the number of isolates of Pseudomonas aeruginosa between groups, though there was a trend towards a lower cumulative isolation rate of Pseudomonas aeruginosa in the prophylaxis group at two and three years and towards a higher rate from four to six years. As the studies reviewed lasted six years or less, conclusions cannot be drawn about the long-term effects of prophylaxis. Authors’ conclusions Anti-staphylococcal antibiotic prophylaxis leads to fewer children having isolates of Staphylococcus aureus, when commenced early in infancy and continued up to six years of age. The clinical importance of this finding is uncertain. Further research may establish whether the trend towards more children with CF with Pseudomonas aeruginosa, after four to six years of prophylaxis, is a chance finding and whether choice of antibiotic or duration of treatment might influence this.